THE USE OF LANGUAGE BY BANDUNG RADIO BROADCASTERS: A STUDY ON REGISTERS - Lia Indriyani, - (2007)
The paper entitled The Use of Language by Bandung Radio Broadcasters: A Study on Registers focuses on the language used by the radio broadcasters in Bandung in the case of the specialties of the registers in five radio stations in Bandung (Ardan 105,9 FM, MQ 102,7 FM, Rase 102,3 FM, OZ 103,1 FM, and Antassalam 103,9 FM) and the association between the specialties of the registers used and the target audiences of those radio stations. The descriptive qualitative method is used in exploring the registers of the broadcasters in the five radio stations mentioned above. Register, based on Spolsky (1998), is "a variety of language that most likely to be used in a specific situation and with particular roles and statuses involved." There are four registers found which can reflect the specialties of a radio, they are: the slogan of the radio stations, the terms used by the broadcasters when referring to themselves, the terms used for addressing their listeners, and the term they use for "song." Data analysis shows that every radio station has its own specialties in terms of language used by the broadcasters. The uniqueness of each radio is derived from the age, education level, social status, and lifestyle of the radio's target audiences. The registers of a radio station with younger target audiences are different from those with adult ones. The registers of a radio station that claims itself as an Islamic radio station is also different from a radio station with lower class target audiences.